Genre and stylistic principle in the organisation of artistic education - Tarchynska, Yulia (Convergences - Journal of Research and Arts Education, 2023)
Artistic education is an important factor in the cultural growth of the nation – the development of personal qualities and abilities. The methodology of teaching music pedagogy is related to the category of musical style. The relevance of this study is conditioned by a broad interpretation of the concept of musical style. Numerous musicological interpretations of the concept outline the range of issues and a growing interest among scholars in the search for promising approaches to understanding musical phenomena and the integration of scientific knowledge. The purpose of the study is to investigate musicological solutions to the problem of style, to identify optimal approaches to building the educational process. The paper analyses various interpretations of the concept of "style" by musicologists. Methods and approaches of teaching musical and practical disciplines are highlighted, including the method of stylistic generalisation, experimental methodology, historical and stylistic approach, concentric approach, genre approach, and the principle of generalisation. As a result of the study, it was concluded that the educational process in the classes of musical and practical training should be built according to genre and stylistic principle – semantic generalisations of the genre in the context of multi-level style features. This paper can be useful for teachers in music education institutions to implement an effective approach to organising the educational process.